Teachers of the Ukrainian Higher (High) Pedagogical Institute Named M. Draghomanova in Prague (1923–1933): a Short Tour of Traced and Untracted Fate. - Zubko, Olga (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2023)
The purpose of the article. Analysis of the completeness of biographies of full-time and part-time staff of the Ukrainian Higher (Higher) Pedagogical Institute named after M. Drahomanov in Prague and its subsidiary institution – Matriculation courses. Research methodology. The research used general scientific and special historical methods. In particular, methods of analysis, synthesis, generalization and classification. The scientific novelty of the study is an illustration of the life paths of emigrants in the context of historical analysis. In the Ukrainian Higher (Higher) Pedagogical Institute named after During the ten years of its activity, M. Drahomanov employed ninety-two specialists, eighty of whom were Ukrainians. Many of them also worked in the staff of the Maturation courses, which were attached to the institute in 1923. Out of eighty Ukrainian biographies, eighteen remain unresearched. Conclusions. In the conditions of todayʼs realities, scientific research is important, first of all, because many names return to history, which require a detailed understanding of their status, namely: a hero, a pioneer or a luminary.